Survival Analysis of Endometrial Cancer Patients With Positive Lymph Nodes. Issue 5 (1st June 2013) - Brown, Aaron P.; Gaffney, David K.; Dodson, Mark K.; Soisson, A. Pat; Belnap, Thomas W.; Alleman, Kerry; Sause, William T.
Abstract : Objective: Patients with endometrial cancer with positive lymph nodes (International Federation of Gynecology and Obstetrics stage IIIC) have a substantially worse prognosis. This study investigates how tumor characteristics and adjuvant treatments influence overall survival (OS) in stage IIIC patients. Methods: This multi-institution, institutional review board–approved study is a retrospective review of 116 patients with surgically staged endometrial cancer with positive lymph nodes treated from 1995 to 2008. The study cohort was evaluated using Kaplan-Meier estimates of OS and proportional hazard modeling. Results: The 5-year OS for all patients was 51%. Administration of adjuvant therapy was associated with improved OS when compared with surgery alone ( P = 0.007). Five-year OS was 40% for patients treated with surgery alone (n = 26), 50% with surgery and chemotherapy (n = 8), 58% with surgery and radiotherapy (n = 43), and 54% with surgery followed by both radiotherapy and chemotherapy (n = 39). Patients who received radiotherapy (n = 82) had improved OS (57%) when compared with patients who did not (n = 34, OS = 42%; P = 0.001). Radiotherapy was associated with improved OS for patients with endometrioid histology, high-grade tumors, and positive para-aortic lymph nodes. Patients with nonendometrioid histology and low-grade tumors who received radiotherapy had a similar OS as those who did not. High-grade tumors ( P < 0.001), nonendometrioid histology ( P = 0.004), and more than 2 positive lymph nodes ( P = 0.01) were associated with a poorer OS. After controlling for patient demographics and tumor characteristics, patients with high-grade tumors and more than 2 positive lymph nodes had a poorer OS, whereas patients who received radiotherapy had improved OS. Conclusions: This large institutional study of patients with lymph node–positive endometrial cancer identified prognostic factors associated with a poor OS. Radiotherapy was associated with improved survival and may be specifically indicated for patients with endometrioid histology, high-grade tumors, and positive para-aortic lymph nodes. We recommend further investigation of adjuvant therapies in randomized clinical trials.